How to help children succeed: the impact of parenting styles on access to quality higher education - Danhong Xu; Yong Gui (The Journal of Chinese Sociology)
Abstract What type of parenting style can help children succeed? Academic discussions on this issue are divided into two different theoretical perspectives: cultural reproduction and cultural mobility. This study uses data from the 2017 Survey on the Social Mentality of Chinese College Students to empirically analyze the impact of parenting styles on children’s access to quality higher education. The results indicate that parenting styles not only act as an intermediary mechanism of family socioeconomic status in influencing children’s access to quality higher education but also have an independent effect. Among the various parenting styles, permissive parenting style is more conducive to children gaining admission to elite universities.